Pectin-based Edible Coatings with Lemongrass Essential Oils for Shelf-life Extension of Papaya - Danar Praseptiangga; Husnawati Fatihah Habibie; Dyah Ayu Ashari; Dea Widyaastuti; Rohula Utami; Lia Umi Khasanah (Advance Sustainable Science Engineering and Technology, 2026)
The urgency of biodegradable packaging as an alternative for plastic-based packaging has been demanding. Accordingly, in this study, the development of pectin-based edible coating incorporated with lemongrass essential oils (LEO) has been done to sustain the physicochemical quality of papaya. The edible coating was prepared by using a simple solution method, while LEO was produced by using the water vapor distillation method. Basically, there are five applied treatments, which are uncoating (control), dip-coating (DC), spray-coating (SC), dip-coating with LEO introduction (DC/LEO1%), and spray-coating LEO incorporation (SC/LEO1%). The physicochemical characteristics of papaya were examined over 12 days of storage. Compared to the control, the application of edible coating was significantly (p < 0.05) enhanced weight loss, pH, ascorbic acid, and yeast and mold counts. Therefore, by mixing pectin-based coating solution with LEO can preserve the quality of papaya for almost more than 12 days at room temperature.